Proceedings of the Boston Area Colloquium in Ancient Philosophy. Vol. XXIV (2008) . (Proceedings of the Boston Area Colloquium in Ancient Philosophy, 2009)
This volume contains papers and commentaries presented to the Boston Area Colloquium in Ancient Philosophy during the academic year 2007-8. The papers discuss a wide range of topics related to Plato and Aristotle. On Plato, topics include false pleasures in the Philebus , the tripartite soul in the Republic , and rhetoric in the Phaedrus , and on Aristotle, the relation of the physical and psychological in De Anima , of virtue and happiness in the Ethics , of body and nature in the Physics , and the role of pros hen in the Metaphysics . One other paper argues for the Aristotelian origin of Stoic determinism.